The Analysis of the Senior High School STEM Students and Non-STEM Students’ Level of Interest towards Learning Biology - Ollero, James; Prudente, Maricar S. (IJCER (International Journal of Chemistry Education Research), 2025)
Students’ interest in learning specific disciplines has long been a subject of educational research due to its potential impact on academic performance. Biology, as a core subject in science education, is often perceived as content heavy and reliant on memorization, which may contribute to declining student engagement. This study investigates the significant predictors of interest in learning biology among senior high school students from both STEM and non-STEM disciplines, based on their demographic and academic profiles such as their grade level, strand, first language, sex, age and their intended course in college. Employing a descriptive-quantitative research design, the study utilized a survey approach with an adapted Likert-scale instrument adapted to measure levels of interest. The majority of respondents were grade 12 students, predominantly from the STEM strand with 132 students while non-STEM disciplines are composed of a total of 88 students, Tagalog ethnicity, female, aged 17 and below, and with intentions to pursue non-biology-related college courses. Results revealed that both STEM and non-STEM students exhibited a comparable level of interest in biology, categorized as “Moderately Agree,” with mean scores of 4.37 and 4.13, respectively. Notably, sex and intended college course emerged as statistically significant predictors of students’ interest in learning biology. These findings suggest that while strand affiliation may not drastically influence interest levels, individual factors such as gender and academic aspirations play a more pivotal role. The study underscores the importance of considering diverse demographic variables in understanding and enhancing student engagement in biology education. Future research is encouraged to explore additional factors that may influence interest, such as instructional methods, classroom environment, and prior academic experiences.